"An Auncient Zelous Gospeller […] Desirous to Do Any Thing to Common Good": Edward Whitchurch and the Reformist Cause in Marian and Elizabethan England. Issue 1 (2nd January 2016) - Lucas, Scott
Abstract : This article examines the last years of the life of the prolific evangelical printer Edward Whitchurch (d. 1562). Although biographers have tended to paint his time under the rule of Queens Mary I and Elizabeth I as chiefly a period of quiescence and inactivity, Whitchurch in fact continued to devote himself, first cautiously under Mary and then more openly and vigorously under Elizabeth, to the evangelical cause he had so long supported. Under Mary, Whitchurch worked to thwart the production of Catholic propaganda and to aid suffering evangelicals, most notably his future wife, Archbishop Cranmer's widow. Upon Elizabeth's accession, Whitchurch zealously dedicated himself to advancing the evangelical cause, both through helping "forward" Protestants into key positions in the newly reestablished Church of England and also by assisting in several printing projects designed to bring important Reformation works before the public. The article highlights particular points of connection between Whitchurch and the evangelical Elizabethan printer Richard Harrison, arguing that Whitchurch played the key role in bringing Harrison into the print trade and sustaining him as he produced two important early Elizabethan texts, the first English translation of John Calvin's Institutes of the Christian Religion and the 1562 folio Great Bible.